2014
DOI: 10.5051/jpis.2014.44.6.274
|View full text |Cite
|
Sign up to set email alerts
|

Association between immunoglobulin G1 againstTannerella forsythiaand reduction in the loss of attachment tissue

Abstract: PurposeTo evaluate whether the levels of immunoglobulin G (IgG) antibody to Tanerella forsythia are associated with periodontal status.MethodsPatients with a diagnosis of chronic periodontitis were considered candidates for the study; thus 80 chronic periodontitis patients and 28 healthy persons (control group) were invited to participate in this investigation. The presence of T. forsythia was detected by polymerase chain reaction (PCR) analysis using primers designed to target the respective 16S rRNA gene seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Unfortunately, in the trials included in this review and as reported in the systematic review by Citterio et al [ 14 ], pocket closure is rarely reported as an outcome. Reporting pocket closure as a result is essential and should be included in future investigations [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, in the trials included in this review and as reported in the systematic review by Citterio et al [ 14 ], pocket closure is rarely reported as an outcome. Reporting pocket closure as a result is essential and should be included in future investigations [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, CAL was poorly evaluated in studies of EPL, which makes it difficult to contrast these results. However, it has been reported that CAL is a parameter that adequately indicates periodontal health [ 15 ]. More clinical trials evaluating CAL in the treatment of EPL are required.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, P. gingivalis and T. forsythia were associated with advanced CAL. The evidence supports the association of these microorganisms with the progression of periodontal disease [34][35][36][37]. Nevertheless, individuals harboring microorganisms in subgingival plaque generally respond with a humoral immune response against them [38].…”
Section: Discussionmentioning
confidence: 53%
“…IgG1 antibody was reported to be elevated to T . forsythia that was related to lower disease measures 49 . In contrast, chronic periodontitis patients showed significantly lower IgG1 and IgG2 antibody to antigens from Capnocytophaga spp 50 .…”
Section: Discussionmentioning
confidence: 92%